Prevalence of acute respiratory infections among under-five children and its association with sociodemographic factors and housing conditions in a rural area of the Bundelkhand region: A cross-sectional study - Amit Patel,; Shobha Chaturvedi,; Mehar Bano,; Aditya Pandey, (Asian Journal of Medical Sciences, 2023)
Background: Acute respiratory infections (ARIs) are a significant public health concern in India, accounting for 15–30% of all fatalities among children younger than 5 years. Aims and Objectives: This study estimated the prevalence of ARI and its association with sociodemographic variables and housing conditions in under-five children in rural Jhansi, Bundelkhand region. Materials and Methods: This community-based cross-sectional analytical study was conducted in the selected Anganwadi Centers in Badagaon Block, Jhansi. Data for sociodemographic factors and housing conditions were collected by interviewing parents or caretakers of under-five children using a semi-structured predesigned and pretested pro forma during a house-to-house visit. The sociodemographic factors considered were the educational status of the parents, occupation of the father, religion of the child, socioeconomic class of the family, age of the child, type of family, and sex of the child. The parameters of housing conditions evaluated were overcrowding, ventilation type of chulha, and type of house. Results: The overall prevalence of ARI was found to be 48.88%. Significant sociodemographic factors for ARIs have been the educational level of the mother (χ2=18.69, P<0.001) and father (χ2=12.02, P<0.001), the working status of the fathers (χ2=17.95, P=0.001), the type of family (χ2=23.88, P<0.001), and the gender (χ2=16.57, P<0.001) of the studied children and the significant environmental housing factors associated with ARIs were overcrowding (χ2=13.61, P≤0.001), ill-ventilated houses (χ2=54.63, P<0.001), type of chulha (χ2=164.31, P≤0.001), and type of house (χ2=4.69, P=0.030). Conclusion: The prevalence of ARI as observed in this study is noteworthy. The study’s findings underscore the significance of enhancing sociodemographic indicators and housing conditions as effective measures for preventing ARI in children.